2023
DOI: 10.24294/can.v6i2.3182
|View full text |Cite
|
Sign up to set email alerts
|

An eco-friendly route for green synthesis of ZnO-CoFe2O4 nanoparticles from cardamom and ginger extract as an efficient electrochemical catalyst for water oxidation

Aynaz Kamyab,
Mir Hadi Banan Khojasteh,
Karim Asadpour-Zeynali

Abstract: Water splitting has been one of the potential techniques as a clean and renewable energy resource for the fulfillment of world energy demands. One of the major aspects of this procedure is the exploitation of efficient and inexpensive electrocatalysts due to the fact that the water oxidation procedure is accompanied by a delayed reaction. In this research, ZnO-CoFe2O4 nanostructure was successfully synthesized via the green method and green resources from cardamom seeds and ginger peels for oxygen evolution re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…According to these researchers, nano-biomaterials are essential for optimizing some medical solutions.Nanoparticles play a significant role in protecting the environment. In a study by Kamyab et al [5] , the use of green resources from cardamom seeds and ginger peels was used to synthesize the ZnO-CoFe2O4 nanostructure by the oxygen evolution reaction (OER), which is environmentally friendly and serves as an effective electrochemical catalyst for the oxidation of water. Another study by Krishnan and Rajendran [6] demonstrated that hydrophilically modified mesoporous PS-MWCNT composites have rapid adsorption and desorption kinetics of xylene isomers, which can effectively remove toxic substances from the environment.…”
mentioning
confidence: 99%
“…According to these researchers, nano-biomaterials are essential for optimizing some medical solutions.Nanoparticles play a significant role in protecting the environment. In a study by Kamyab et al [5] , the use of green resources from cardamom seeds and ginger peels was used to synthesize the ZnO-CoFe2O4 nanostructure by the oxygen evolution reaction (OER), which is environmentally friendly and serves as an effective electrochemical catalyst for the oxidation of water. Another study by Krishnan and Rajendran [6] demonstrated that hydrophilically modified mesoporous PS-MWCNT composites have rapid adsorption and desorption kinetics of xylene isomers, which can effectively remove toxic substances from the environment.…”
mentioning
confidence: 99%